A CRYPTOLEPIS SANGUINOLENTA-BASED PREPARATION REDUCED HOSPITAL STAY AND MORTALITY OF COVID-19 PATIENTS DURING THE PANDEMIC - MUTOCHELUH , Mohamed; ANSAH, Charles; BUABENG, Kwame; TWUMASI-ANKRAH, Sampson; DOMFEH, Seth; OWUSU, Michael; OWUSU-ANSAH, Michael; BORQUAYE, Lawrence; ADEI, Evans; DUAH, Christiana; BOAMAH, Daniel; BOAKYE-YIADOM , Mavis; et al. (African Journal of Traditional, Complementary and Alternative Medicines, 2025)
Background: In 2020, the World Health Organization urged nations to take domestic steps to curb the spread and contain the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) pandemic, also referred to as coronavirus disease 2019 (COVID-19). In the meantime, there was growing clinical evidence that reported favourable effects of using herbal medicine in managing COVID-19. We, therefore, repurposed Nibima (a Cryptolepis sanguinolenta-based herbal preparation) as an adjunct to conventional therapy for COVID-19. This was premised on our previous in vitro investigations that showed that Nibima has both antiviral and anti-inflammatory activities. Materials and Methods: This trial (FDA/CT/11) was an open-label, randomised controlled phase II pilot study, which was conducted from March 2021 to October 2022 among hospitalised COVID-19 patients in the Ashanti Region of Ghana. Participants were either randomised to aqua (water) or Nibima, the investigational product as adjunct to COVID therapy. Results: Nibima was well tolerated by the study participants, and the patients who were administered that together with the standard COVID-19 therapy had rapid clinical recovery compared to those taking aqua and the standard or conventional COVID-19 therapy. The evidence obtained provides a strong basis for future studies with large numbers of hospitalised patients with COVID-19 and other viral respiratory infections. Conclusion: Though COVID-19 is no longer a pandemic, it is still a public health challenge. We recommend that Nibima be further investigated for its broad-spectrum antiviral and immunomodulatory activities against SARS-COV-2 and other viral infections in preparedness for the re-emergence of future pandemics.